PERSEPSI AKAN #UMROH DAN #UMRAH DI TWITTER: MEDIA SOSIAL DAN INDUSTRI PARIWISATA - Nuki Mayasari (UIN Sayyid Ali Rahmatullah Tulungagung, 2019)
Listed as a “lower middle income” country in 2013 (World Bank, 2013), Indonesia increases its status to be a “middle income” country in 2019 (World Bank, 2019). Furthermore, the increase of economic status is still accompanied with a high frequency of umrah trips. Nowadays, umrah trips is marked by a wide variety of trips package promoted by national as well as international travel agencies, offerings myriads of choices from an economic umrah package to the luxurious one. This could also be a sign that umrah is not only popular in Indonesia, but also well-known internationally. In this writing, I will present a research on #Umroh and #Umrah hashtags in Twitter, in representing the dynamics of umrah trips. Using Critical Discourse Analysis (CDA) methods, this research suggests social media have a role in shaping umrah trips. Furthermore, umrah trips tightly related to the concept of tourism industry. Keywords: Umrah Trips, Twitter, Hashtag, UGC, CDA, Advertisement, Industry